The changing use of disease-modifying anti-rheumatic drugs in individuals with rheumatoid arthritis from the United Kingdom General Practice Research Database. - Edwards, C; Arden, N; Fisher, D; Saperia, J; Reading, I; Van Staa, T; Cooper, C (2005)
OBJECTIVES: To describe the use of disease-modifying anti-rheumatic drugs (DMARDs) in the treatment of rheumatoid arthritis (RA) and changing trends in their use. METHODS: We used the General Practice Research Database (GPRD) to describe DMARD use by patients with RA identified using ICD-9 codes. The GPRD is a UK national database containing records of more than 7 million individuals from 683 general practices. Subjects were studied between 1987 and 2002. The prevalence and duration of individual DMARD use and changing trends in DMARD use were investigated. RESULTS: Thirty-four thousand three hundred and sixty-four patients with RA were identified. Only 17,115 (50%) individuals were prescribed at least one DMARD during the study period. The most commonly prescribed DMARD over the study period was sulphasalazine (46.3%) and then methotrexate (31.4%). Use of methotrexate has increased 17-fold (1.8% of all DMARD prescriptions in 1988 to 30% in 2002) whereas use of gold has fallen (13.2% to 2.3%). Analysis of DMARD persistence using Kaplan-Meier survival curves showed the methotrexate use persisted significantly longer than other DMARDs with an estimated median of 8.1 yr. Prednisolone was used in up to 50% of RA patients in any one year and has remained fairly constant throughout the study period. CONCLUSIONS: Large numbers of individuals with a clinical diagnosis of RA identified from a large primary care database are not receiving DMARDs. This work suggests that many individuals with RA have not been treated appropriately and this may have major long-term consequences on joint damage and general health.